The relationship between bullying and mental exhaustion (Burnout Syndrome) in educators - Freire, Paula Ariane [UNESP] (Assoc Servidores Arquivo Nacional, 2015)
The modes of post-Fordist management and the flexibility of labor rights engendered by the productive restructuring, bring changes in the workplace, with more control over work and imposition of goals. The school environment has also suffered the impacts of this restructuring process. There is greater control over the teaching activities, both in relation to how to teach lessons about the taught contents and forms of assessment, as well as exhaustive working hours. These new working conditions may favor the practice of bullying, a process of psychological violence against teachers, which threatens their fundamental human rights as well as their health, which can bring, as a result, several psychiatric diseases, among which the Syndrome Burnout. It is estimated that 15% of teachers suffer from this syndrome - one work-related disorder caused by chronic job stress - whose symptoms are: low job satisfaction, emotional exhaustion and depersonalization, which appears in the form of emotional hardening and lack of empathy. This project aims to investigate the relationship between productive restructuring, bullying and the incidence of burnout syndrome in teachers and their educational and sociological impacts.
Keywords: Mobbing; Burnout Syndrome; teaching work